SUPPLY CHAIN MANAGEMEN PENGARUHNYA PADA KINERJA UMKM PADA SENTRA PENGOLAHAN HASIL PERIKANAN DESA KOTO MESJID KECAMATAN XIII KOTO KAMPAR - Zulher, Suarni Norawati (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Abstract :This research was conducted at UMKMwhich is at the center of fisheries product processing village Koto Mesjid district XIII Koto Kampar. The purpose of this study was to determine the effect supply chant management against performance UMKM. The sample olf this study was all owners UMKMther are as many fishery products processing centers 12 UMKM. Analysis is done using simle linear regression and hypothesis testing is done by using the t test alpha 5%. Based on the results of research and discussion it can be concluded that is performance UMKM which is under the supervision of the fisheries center village Koto Mesjid District XIII Koto Kampar based on the results of the descriptive analysis in the good category and so for the variables supply chant management which is also in the good category. Supply chant management has a significant influence on performance UMKM this can be seen in the results of the t test which is significant at the level of confidence 95%. Supply chant management having a very close relationship with performance UMKM which is under the supervision of fisheries centers village Koto Mesjid District XIII Koto Kampar, this can be seen from the correlation coefficient obtained for 89,6%. Keyword : Performance UMKM, Supply Chant Management